Role of cytogenetic profiles as prognostic factors for complete remission after induction phase in acute myeloblastic leukemia - Hikari Ambara Sjakti; Gatot Djajadiman; Pustika Amalia Wahidiyat; Agus Kosasih; Iswari Setianingsih (Indonesian Pediatric Society, 2021)
Background Risk stratification for acute myeloid leukemia (AML) in children is a must in treatment strategy. This stratification is based on cytogenetic profiles, which are needed to determine proper management to gain better outcomes and reduce side effects of treatment. There is no such risk stratification available in Indonesia until now. Objective To evaluate the association between cytogenetic profiles of t(8,21) and inv(16) mutations with the complete response to induction phase of chemotherapy in pediatric AML. Methods A prospective study was conducted between year 2018 and 2020, involving children with AML from 4 pediatric oncology centers in Jakarta. Subjects were evaluated for cytogenetic profiles, especially t(8,21) and inv(16), as the favorable predictors for AML. Bone marrow remission was evaluated after 2 cycles of induction phase. The results were evaluated for remission rate and survival analysis. Results Karyotype data of 18 subjects were obtained. Translocation t(8;21) detected in 1 subject, and inv(16) mutation in 4 subjects. These two variables had no significant correlation with complete remission after induction phase. Nevertheless, favorable group had more tendencies to achieved remission than unfavorable group. Complete remission achieved in 61% subjects, 90% of theme had a relapse period with an average time 43 weeks. The relapse period in favorable group was shoter than in unfavorable group (34 weeks and 44 weeks, respectively). Conclusions This study shows that cytogenetic profiles of t(8;21) and inv(16) mutation can not be used as prognostic factors for complete remission after induction phase of chemotherapy in pediatric AML.